Jurnal BUSINESS & ENTREPRENEURSHIP: the influence of socio demographic factors on job streess level in foreign owned manufacturing companies in ogun state. Nigeria - Ajibade david (SB-IPB, 2016)
penelitian ini menguji pengaruh faktor sosio demografis pada tingkat stress kerja di perusahaan manufaktur milik asing di Ogun